การถ่ายทอดเทคโนโลยีนวัตกรรมข้าวนาโยนของกลุ่มผู้ประกอบการข้าวแบบมีส่วนร่วม - อินทุวงศ์ กันต์ (RMUTP Research Journal Sciences and Technology, 2015)
บทคัดย่อ การวิจัยนี้มีวัตถุประสงค์ เพื่อถ่ายทอดเทคโนโลยีนวัตกรรมข้าวนาโยนของกลุ่มผู้ประกอบการข้าวแบบมีส่วนร่วม โดยใช้ด้วยรูปแบบการจัดการองค์ความรู้สู่ชุมชน (KM): ภาคปฏิบัติชุมชนด้วยการวิจัยเชิงปฏิบัติการ (Action Research) โดยใช้วิธีการเลือกสุ่มตัวอย่างแบบเจาะจง จากในพื้นที่ จ.อุตรดิตถ์ จำนวน 40 คน ทั้งหมด 5 ช่วงกิจกรรม คือ Education of Knowledge, Knowledge Work Rally, Cooperative Work Shop, Mind Mapping Work Shop และ Evaluation Program โดยใช้สถิติสถิติเชิงพรรณนาในการวิเคราะห์ข้อมูล ใช้วิธีการวิเคราะห์เนื้อหา (Content Analysis) ด้วยค่าร้อยละ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน ผลการทดลองพบว่า ส่วนใหญ่เกษตรกรเป็นเพศชาย อายุ 41-50 ปี ส่วนใหญ่แต่งงานแล้ว ระดับการศึกษา ป.4-ป.6 ใช้แรงงานในครัวเรือนเฉลี่ยในการประกอบการนี้ ครอบครัวละ 4 คน แต่มีความรู้ด้านนี้ต่ำกว่า 3 ปี แต่มีความต้องการนวัตกรรมนี้ในระดับมากร้อยละ 73.5 ส่วนใหญ่เป็นสมาชิกของกลุ่มเกษตรกร รองลงมาเป็นสมาชิกของ ธ.ก.ส ที่ส่วนใหญ่มีอาชีพทำนา เน้นด้านนวัตกรรมเครื่องบดดิน, นวัตกรรมเครื่องโรยดิน และ นวัตกรรมเครื่องหยอดเมล็ดพันธุ์ข้าว มีความพึงพอใจ:ภาคปฏิบัติชุมชน ส่วนใหญ่มีความพึงพอใจในโครงการ KMและมีความรู้ความเข้าใจของโครงการในภาพรวมอยู่ในระดับดีมากที่สุด มีค่าเฉลี่ย ( = 4.56,SD = 0.49 ) Abstract This research aimed to transfer the participatory rice parachute innovation for rice entrepreneur group by using principles of Knowledge Management in Action in Community (Action Research). Forty people of Uttraradit Province were purposively sampled to participate in five phases of the activities as follows; the Education of Knowledge, the Knowledge Work Rally, the Cooperative Work Shop, the Mind Mapping Work Shop, and the Evaluation Program. The data analysis was done by descriptive statistics and content analysis method for qualitative information. The information was calculated by percentage, mean (), and standard deviation (S.D.). Most farmer samples were male with the age from 41-50 years, married and their educational level at Primary 4 to 6. The average household labor for this activity was four people. Their experiences regarding to this innovations were less than three years, but 73.5 percent of them were interested in the innovations. Most of them were members of the agriculturist groups, followed by the members of Bank for Agriculture and Agricultural Cooperatives. The innovations were regarded to termite soil grinder, soil sprinkler, and rice-seeder. The overall satisfaction towards KM had the highest level of satisfaction and understanding with mean of = 4.56, SD= 0.49.